Transcriptome Analysis of Ivosidenib-Mediated Inhibitory Functions on Non-Small Cell Lung Cancer - Wu, Juan; Chen, Ru; Shen, Huiqing; Yan, Ting; Qian, Yu; Zhang, Yaping; Huang, Zhuoya; Kong, Pengzhou; Pang, Min; Zhang, Xinri (Frontiers in Oncology, 2021)
Ivosidenib, one Isocitrate Dehydrogenase (NADP(+) 1 (IDH1) mutant inhibitor recently was approved by the Food and Drug Administration (FDA) for leukemia and studies suggested that it may inhibit the progression of non-small cell lung cancer (NSCLC). In the present study, we aimed to explore key RNAs and their potential regulatory mechanisms induced by Ivosidenib treatment in NSCLC cells. MTT assay, transwell assay and flow cytometry were used to detect the anti-tumor effects of Ivosidenib on NSCLC cells. Furthermore, whole transcriptome sequencing was performed to detect the common differentially expressed mRNAs (DE-mRNAs) and non-coding RNAs (ncRNA). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were performed to investigate the biological functions and potential mechanisms. Based on miRNA target interactions, a competing endogenous network was constructed. The results showed that Ivosidenib inhibited the proliferation, invasive and migration of NSCLC cells. A total of 212 DE-mRNAs, 4 DE-miRNAs, and 206 DE-lncRNAs were identified in the Ivosidenib-treated NSCLC cells compared to the untreated NSCLC cells. DE-mRNAs were significantly enriched in cancer-associated pathway, such as TGF-β signaling pathway, PI3K-Akt signaling pathway, Jak-STAT signaling pathway, MAPK signaling pathway, Rap1 signaling pathway and cell adhesion molecules. Based on the theory of competing endogenous RNA, the lncRNA–miRNA–mRNA networks were constructed to clarify the regulatory relationship between ncRNA and mRNA. Moreover, qRT-PCR results showed consistent expression trends of differential genes with transcriptome analysis.Our results provided useful information about the molecular basis of Ivosidenib in suppressing NSCLC.